2014
DOI: 10.1016/j.ypmed.2014.10.008
|View full text |Cite
|
Sign up to set email alerts
|

School food reduces household income disparities in adolescents' frequency of fruit and vegetable intake

Abstract: Objective To examine whether school food attenuates household income-related disparities in adolescents’ frequency of fruit and vegetable intake (FVI). Method Telephone surveys were conducted between 2007–2008 with adolescent-parent dyads from Northern New England; participants were randomly assigned to be surveyed at different times throughout the year. The main analysis comprised 1,542 adolescents who typically obtained breakfast/lunch at school at least once/week. FVI was measured using 7-day recall of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 40 publications
2
27
1
Order By: Relevance
“…Parents and children reported a greater frequency of weekly consumption of fruits and sweets/desserts categories during summer versus school. These findings are in contrast to other studies either reporting lower frequency in consumption of fruit and vegetables during summer compared to school months, or concluding no dietary differences exist between summer and school months . The data shows children are consuming sweets and desserts (eg, candy, doughnuts, cookies etc) on average 6 out of 7 days per week during the summer, compared to school where this frequency drops to 2.5 days per week.…”
Section: Discussioncontrasting
confidence: 97%
“…Parents and children reported a greater frequency of weekly consumption of fruits and sweets/desserts categories during summer versus school. These findings are in contrast to other studies either reporting lower frequency in consumption of fruit and vegetables during summer compared to school months, or concluding no dietary differences exist between summer and school months . The data shows children are consuming sweets and desserts (eg, candy, doughnuts, cookies etc) on average 6 out of 7 days per week during the summer, compared to school where this frequency drops to 2.5 days per week.…”
Section: Discussioncontrasting
confidence: 97%
“…These authors suggested that school lunches might also be useful in preventing inequity in children's dietary intake due to the socio-economic status of their family (22) . This effect is also expected in the USA (23,24) .…”
Section: Discussionsupporting
confidence: 73%
“…Early identification of individuals with HIV seroconversion among PWID in Miami, most of whom use both opioids and stimulants known to increase injection frequency and high risk behaviors [22], helped drive collaboration between a privately funded SSP and the health department at the county and state levels to investigate the HIV transmission network in Miami. With the HIV outbreak and response in Scott County, Indiana, investigators determined that early surveillance efforts could reduce emerging epidemics [18,23]. In Miami-Dade County, the implementation of routine screening at the SSP, early identification of individuals with recent seroconversion, and subsequent investigation helped establish low-threshold routes of access to HIV care for PWID to mitigate further transmission of HIV within the community.…”
Section: Discussionmentioning
confidence: 99%